ROMANTIKA MANUSIA MELAYU DI BANDAR RAYA (IMAJI-IMAJI KEHIDUPAN KOTA DALAM KOMIK KARTUN MALAYSIA-INDONESIA) - Budiyanto, Ary; Wicandra, Obed Bima (Institute of Research and Community Outreach - Petra Christian University, 2008)
A big city or a metropolitan is a symbol of modernization and globalization. What happens in a big city in this article is stories of ordinary people struggling for a decent living in the dusts of global modernity in a big Malay city. These people are often village migrants. The attraction of modern city lifestyle offers cultural addiction that is foreign for the migrants, even if sometimes it is considered a threat culturally from where they are from. Eventually, adaptation, adoption, and even apathy towards values, symbol, and the cityâ€™s global modernity create diverse lifestyles, romances, and identities of its citizens. This article observes how the citizens, the city, and its romance present in the reflections of some Malaysian and Indonesian cartoonists, like in the visualization of the comic â€œMat Somâ€ by Dato Lat, and the comic script Keeâ€™s World (1989) of Malaysia and Benny and Mice of Indonesia. Cartoonists, as social observers, tell us how the city is recognized in the lives of the Malay people in two different countries. Abstract in Bahasa Indonesia: Kota Besar atau Bandar Raya modern adalah simbol dari modernisasi dan globalisasi. Apa yang terjadi di sebuah kota besar di artikel ini adalah cerita-cerita orang biasa yang mencari kehidupan yang layak dalam debu modernitas global di kota besar dunia melayu. Tak jarang mereka adalah orang yang datang dari kampung (atau luar daerah). Pikatan gaya hidup kota modern ini menawarkan candu budaya yang â€˜asingâ€™ bagi pendatang, meski tak jarang hal itu dianggap â€˜ancamanâ€™ bagi budaya â€˜asalâ€™. Akhirnya, adaptasi, adopsi, maupun, antipati pada nilai-nilai, simbol, modernitas global perkotaan itupun menciptakan keberagaman gaya hidup, romantika, dan identitas penghuni kota. Artikel ini akan melihat bagaimana penghuni kota, kota, dan romantikanya hadir dalam renungan-renungan para kartunis malasyia dan Indonesia seperti, di antaranya, dalam visualisasinya komik â€œMat Somâ€ karya Dato Lat dan komik Script Keeâ€™s World (1989) Malaysia dan Benny & Mice Indonesia. Kartunis, sebagai pengamat sosial, menuturkan pada kita bagaimana kota dihayati dalam kehidupan bangsa melayu di dua negara yang berbeda. Kata kunci: romantika kota, narasi visual, komik, Malaysia, Indonesia.